Neuroimaging of Cerebral Ischemia and Infarction - Leiva-Salinas, Carlos (Springer-Verlag, 2011)
The imaging workup for patients with suspected acute ischemic stroke has advanced significantly over the past few years. Evaluation is no longer limited to noncontrast computed tomography, but now frequently also includes vascular and perfusion imaging. Although acute stroke imaging has made significant progress in the last few decades with the development of multimodal approaches, there are still many unanswered questions regarding their appropriate use in the setting of daily patient care. It is important for all physicians taking care of stroke patients to be familiar with current multimodal computed tomography and magnetic resonance imaging techniques, including their strengths, limitations, and their role in guiding therapy. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13311-010-0004-2) contains supplementary material, which is available to authorized users.